ISO 9001 certification in a public institution for education and agricultural research: a case study (Research, Society and Development, 2022)
Many Brazilian public institutions have invested in quality certification with the adoption of the international standard ISO 9001 to meet research and educational demands focused on the development of the agricultural sector. This work aims to analyze existing conditions in the Crop Sector (SGC) of the Plant Science Department of the Universidade Federal Rural do Rio de Janeiro (UFRRJ) and diagnose non-conformities with ISO 9001 standard as well as submit developed methods to the first-party audit. The existent conditions at the agricultural facilities were assessed, therefore diagnosing non-conformities accordingly to ISO 9001 standard requirements and, as a result, establishing a traceable method that complies with the normative requirements. Certification of conformity from the quality management system was granted to the developed methods by a first-party audit. As a conclusion we can say that the certification of SGC may advance the development of future institutional policies focused on renewal, continuous qualification of staff, increased efficiency and operational sustainability, closer relations with public and private institutions, development of a sustainable culture, and constant pursuit for excellence in the quality of products and services provided. The experiences reported in this study may collaborate to promote quality management in other public institutions focused on agricultural activity.